Exploring the Feasibility of Supporting UK Partners Living Alongside Veterans with PTSD: A Pilot Study of the Together Programme (TTP) - Dominic Murphy; Lucy Spencer-Harper; David Turgoose (Journal of Family Medicine, 2019)
Background Romantic partners living alongside veterans with Post Traumatic Stress Disorder (PTSD) appear at increased risk of secondary traumatic stress (sPTSD) and common mental health difficulties (CMD) compared to the general population. The severity of symptoms implies the need for structured, bespoke and evidence-based interventions. Objective The aim of this study was to explore the feasibility of offering a community support programme (The Together Programme, TTP) for military partners. TTP was developed based upon a number of US programmes and consisted of 10 hours of group-based support delivered over a five-week course. 56 participants engaged in TTP over a year at nine locations across the UK and were followed up three months later. Methods Measures of CMD, sPTSD, alcohol use and relationship satisfaction were used to assess benefits. Data were also collected on attendance and participant feedback. Results Significant reductions were observed for symptoms of sPTSD and CMD at follow up. 51/56 (90.1%) participants completed TTP. The majority of participants reported positive experiences. However, several individuals stated wanting more sessions and that barriers such as work, and family commitments made it difficult to attend. Conclusions Whilst limitations exist, the data presented suggests cautious optimism for the efficacy of offering a structured programme of support to address the needs of military partners living alongside PTSD.
Keywords: traumatic stress